Beneficial Effects of Selective Orexin-A Receptor Antagonist in 4-aminopyridine-induced Seizures in Male Rats - Parichehr Hayatdavoudi; Hamid-Reza Sadeghnia; Nema Mohamadian-Roshan; Mousa AL-Reza Hadjzadeh (Advanced Biomedical Research, 2017)
Background: Orexins are excitatory neuropeptides which stimulate the central regulatory pathways. Orexins increase the penicillin-induced epileptic activity in rats. Orexin-A increases in different types of seizures and its elevated level is the characteristic feature in the epileptic children during polysomnography. Recently, the orexin receptor blockage has been reported to increase seizure threshold in mice; however, effect of the selective orexin-A receptor antagonist (SB-334867) on 4-aminopyridine (4-AP)-induced seizures has not been investigated. Materials and Methods: We used the intraperitoneal injection of 4-AP to induce seizure in male rats. Under urethane anesthesia, SB-334867 (50 and 100 nmol) was injected stereotaxically into the ventral hippocampal commissure. Using video recording, the effects of SB-334867 on electroencephalogram and tonic–clonic convulsions were compared to those that received diazepam or dimethyl sulfoxide (DMSO). Results: SB-334867 significantly decreased the duration of spike trains compared to DMSO-treated rats (P < 0.001) and reduced the duration of convulsive seizures (P < 0.05). Seizure onset was increased significantly by SB-334867, 50 nmol, compared to DMSO (P < 0.05) and diazepam (P < 0.01) treated rats. Conclusion: Antagonism of orexin-A receptor by a low-dose SB-334867 showed protective effects in 4-AP-induced seizure-like activities in anesthetized rats.